Female Genital Schistosomiasis: A Neglected among the Neglected Tropical Diseases - Benedetta Rossi; Letizia Previtali; Martina Salvi; Roberta Gerami; Lina Rachele Tomasoni; Eugenia Quiros-Roldan (Microorganisms, 2024)
Schistosomiasis is a neglected parasitic disease linked to water, posing a global public health concern with a significant burden in sub-Saharan Africa. It is transmitted by Schistosoma spp., causing both acute and chronic effects affecting the urogenital or the hepato-intestinal system. Through granuloma formation, chronic schistosomiasis weakens host immunity, heightening susceptibility to coinfections. Notably, female genital schistosomiasis (FGS), a disregarded gynecological condition, adversely affects girls’ and women’s reproductive health and increases vulnerability to HIV. This review explores the intricate interplay between schistosomiasis and HIV, considering their geographical overlap. We delve into the clinical features of this coinfection, underlying mutual influences on transmission, diagnostic challenges, and therapeutic approaches. Understanding the dynamics of FGS and HIV coinfection is pivotal for integrated healthcare strategies in regions with co-endemicity, aiming to mitigate the impact of the two infections on vulnerable populations.